Penentuan Kadar Besi (Fe), Mangan (Mn), dan Timbal (Pb) dalam Sampel Air Minum Menggunakan Atomic Absorption Spectrophotometry (AAS) - Vivi Aprilia Putri; Syamsi Aini (MASALIQ, 2025)
This study aims to determine the concentrations of heavy metals—iron (Fe), manganese (Mn), and lead (Pb) in drinking water samples using the Atomic Absorption Spectrophotometry (AAS) method. The research employed a descriptive quantitative approach, involving the preparation of standard solutions and the analysis of filtered drinking water samples. Measurement results indicated that the concentrations of Fe (–0.3714 mg/L), Mn (–0.1098 mg/L), and Pb (–0.5218 mg/L) were below the instrument’s detection limit, resulting in negative values. These findings suggest that the levels of heavy metals in the samples are extremely low and well below the maximum limits set by the Regulation of the Minister of Health of the Republic of Indonesia No. 2 of 2023: 0.3 mg/L for Fe, 0.1 mg/L for Mn, and 0.01 mg/L for Pb. The study concludes that the tested drinking water samples meet quality standards and are safe for consumption, posing no health risks from heavy metal exposure. Additionally, AAS proved to be an effective method for detecting trace metal concentrations, making it suitable for regular and sustainable water quality monitoring.